(untitled) (Research Announcements "Heritage BG", 2025)
The study aimed to evaluate the level of motor development, based on the monitoring of anthropometric indicators: height, weight, and chest circumference by organizing systematic swimming lessons for children in the initial stage of the basic educational level. The benchmarking analysis of the learning results was carried out within one academic year. The subject of the analysis is the influence of primary swimming training on children’s health condition and motor development in the initial stage of the basic educational level. The object of research is the dynamics of anthropometric indicators in the process of swimming training, as well as the tracking of specific indicators measured with objective instruments, their systematization, and analysis. Scientifically based conclusions will allow us to establish the influence of motor training of students on the dynamics of their anthropometric indicators: height, weight, and chest circumference through systematic swimming activities. An analysis of the dynamics through mathematical-statistical processing was applied to derive the interrelationship between the indicators. References: Nesheva 2023: Nesheva, Irina. A wellness tооl to perform healthy lifestyle practices In the Bulgarian school system. Natsionalno izdatelstvo Az Buki MON Sp. „Strategii na obrazovatelnata i nauchna politika“ S. tom 31, nomer 5, 560-572, ISSN 1314–8575 (Online); ISSN 1310–0270 (Print) – 0.2 (2022) Impact factor/ Q4 (2022) Rank by JCI, https://doi.org/10.53656/str2023-5-7-wel Angelova 2023: Angelova, Petia. Overview of the research activity of the department of physical education and sports at trakia university Trakia Journal of Sciences, Vol. 21, Suppl. 1, 420-424, Trakia University, Available online at: http://www.uni-sz.bg ISSN 1313-3551 (online) doi: 10.15547/tjs.2023.s.01.070 Angelova 2021: Angelova, Petia. Rоle of respiratory rehabilitation in patients recovering from coronavirus infection covid-19 Trakia Journal of Sciences, Vol. 19, Suppl. 2, 29-32, Copyright © 2021 Trakia University Available online at: http://www.uni-sz.bg ISSN 1313-3551 (online) doi: 10.15547/tjs.2021.s.02.006 Angelova 2021а: Angelova, Petia. Study and comparative analysis of body weight indicator data in women students Trakia Journal of Sciences, Vol. 19, Suppl. 1, 654-658, Copyright © 2021 Trakia University Available online at: http://www.uni-sz.bg ISSN 1313-3551 (online) doi: 10.15547/tjs.2021.s.01.100 Dimitrova 2020: Dimitrova, Bistra. Relation ships between education and innovations in the recreation Industry in Bulgaria. DOI: 10.15547 / tjs.2019.02.007. Trakia Journal of Sciences, Vol. 18, No 2, 2020, 143-149, ISSN: 1313-3551 (online). Available at: http://tru.uni-sz.bg/tsj/Vol.18 Dimitrova 2019: Dimitrova, Bistra. Quality assessment about standards for wellness services and certified skills of specialized staff. DOI: 10.15547 / tjs.2019.02.007. Trakia Journal of Sciences, Vol. 17, No 2, 2019, 143-149, ISSN: 1313-3551 (online). Available at: http://tru.uni-sz.bg/tsj/Vol.17 Dimitrova 2019.a: Dimitrova, Bistra. New smart educational model ‘Wellness instructor’. Monograph. Ed. Avangard Prima, Sofia, first edition. ISBN: 978-619-239-150-8 Ignatova 2018: Ignatova, Darinka. The effects of swimming on preschool children with spinal abnormalities, 17th International Balkan Society for Pedagogy and Education /BASOPED/ Conference ‘Traditions and innovations in the education of the Balkan countries’, ISBN 978-954-326-370-7, Sofia, 207-212. Ignatova 2021: Ignatova, Darinka. Specificity of the motor potential for achieving Scholar Wellness, Trakia Journal of Sciences, Vol. 19, Suppl. 1, 867 873, ISSN 1313-3551 (online), Trakia University doi: 10.15547/tjs.2021.s.01.136, Available online at: http://www.uni-sz.bg Ignatova & Iliev 2023: Ignatova, Darinka, Alexander Iliev. Current methods and models combining nutritional regimes with motor activity. International Scientific Journal of Innovation “Smart Innovations in the Recreational (Wellness) Industry and Niche Tourism”, ISSN: 2603-4921, 05 (1-2), 08 14, https://scjournal.globalwaterhealth.org/wp-content/uploads/2024/02/2.IGNATOVA_ILIEV_p.7-13_2023.pdf Nesheva 2023а: Nesheva, Irina. Pregnancy and wellbeing. Trakia Journal of Sciences, Sofia. Volume 21, Supplement 1, Series Social Sciences, 231-235, doi: 10.15547/tjs.2023.s.01.039 ISSN 1313-7069 (print), ISSN 1313-3551 (online) Nesheva 2022: Nesheva, Irina. Social benefits of Wellness motor activities for women with normal pregnancy. International Scientific Journal of Innovation “Smart Innovations in the Recreational (Wellness) Industry and Niche Tourism”. Vol. 4, Is. 1-2, ISSN: 2603-4921, 22-27.